Genome-scale metabolic model led engineering of Nothapodytes nimmoniana plant cells for high camptothecin production - Murali, Sarayu; Ibrahim, Maziya; Rajendran, Hemalatha; Shagun, Shagun; Masakapalli, Shyam Kumar; Raman, Karthik; Srivastava, Smita (Frontiers in Plant Science, 2023)
Camptothecin (CPT) is a vital monoterpene indole alkaloid used in anti-cancer therapeutics, primarily derived from Camptotheca acuminata and Nothapodytes nimmoniana plants that are indigenous to South-east Asia. Plants have intricate metabolic networks and deciphering them to produce secondary metabolites, such as CPT, is a prerequisite of rational metabolic engineering design for optimizing their production. By reconstructing metabolic models, we can predict plant metabolic behaviour, facilitating the selection of suitable approaches, saving time, cost, and energy, over traditional hit and trial experimental approaches. In this work, we reconstructed a genome-scale metabolic model for N. nimmoniana (NothaGEM iSM1809) and curated it with biochemical data obtained experimentally. We also used in silico tools to identify and rank suitable enzyme targets for over-expression and knock-out to maximize camptothecin production. The predicted over-expression targets encompass enzymes involved in the camptothecin biosynthesis pathway, including strictosidine synthase and geraniol 10-hydroxylase, as well as targets related to the plant's metabolism, such as amino acid biosynthesis and tricarboxylic acid cycle. The top-ranked knock-out targets include reactions responsible for the formation of folates and serine, as well as the conversion of acetyl CoA and oxaloacetate to malate and citrate. One of the top-ranked over-expression targets, strictosidine synthase was chosen to generate metabolically engineered cell lines of N. nimmoniana using Agrobacterium tumefaciens mediated transformation. The transformed cell line showed a 5fold increase in camptothecin production with a yield of up to 5 µg g -1 .